Microsurgical clipping of a ruptured lobulated anterior communicating artery aneurysm arising from a fenestrated complex: a case report - Shahma, Abu; Chagla, Aadil S.; Tyagi, Devendra K.; Rathore, Nakul (International Journal of Research in Medical Sciences, 2026)
Fenestrations of the anterior communicating artery (ACOM) are uncommon vascular variants that predispose to aneurysm formation due to structural defects and altered hemodynamics. Their association with lobulated, broad-neck aneurysms creates significant diagnostic and surgical challenges. Herein this case reports a case of a 60-year-old woman with hypertension and diabetes presented with World Federation of Neurosurgical Societies grade IV subarachnoid hemorrhage. Digital subtraction angiography revealed a lobulated aneurysm with a broad neck (4.8 mm) arising from the superior limb of a fenestrated ACOM complex. Emergency left pterional craniotomy was performed. Sequential clipping was employed: a 9 mm straight clip remodeled the aneurysmal neck and secured a perforator, followed by a 4-mm fenestrated clip across the neck for complete obliteration. Indocyanine green angiography confirmed aneurysm exclusion with preservation of parent vessels and perforators. Postoperatively, the patient showed modest neurological improvement but succumbed on day 19 due to ventilator-associated pneumonia and comorbidities. Fenestrated, lobulated ACOM aneurysms are technically demanding. Tailored clip strategies, careful preservation of perforators, and intraoperative angiography are crucial for safe and effective microsurgical management.